Achieving Social Competence for Prospective Teachers: Campus Teaching Experience and Communication Ability - Azzahra, Tiffany Diahnisa; Patmisari, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
One part of the Independent Campus Learning Program (MBKM) is the Teaching Campus Program. Teaching Campus is a program initiated by the Ministry of Education and Culture to serve the academic community in schools. This program provides students with the experience of being part of the teaching and learning process in the classroom. This research aims to determine the influence of the Teaching Campus Program and communication skills in improving the social competence of prospective teachers. This research uses quantitative research methods with a correlational design. The research sample consisted of 59 students from the Faculty of Teacher Training and Education using the combined sampling method. The data analysis technique uses multiple regression with the help of SPSS 26 for Windows. The results of the research show that (1) the Teaching Campus Program influences the social competence of prospective teachers with a significance value of 0.038 < 0.05, (2) communication skills influence the social competence of prospective teachers with a significance value of 0.000 < 0.05, (3) the Campus Program Teaching and communication skills influence the social competence of prospective teachers with a significance value of 0.000 < 0.005.